Smart wheelchair / Nur Syahirah Ramli … [et al.] - Ramli, Nur Syahirah; Latif, Siti Alya Hanisah; Ahmad Syahrani, Nur Izzah Syahmina; Idris, Nurul Jannah; Mohd Nazri, Syalwina Auni; Harudin, Muhammad Jeff Aiman; Abas, Norlela (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Wheelchairs have long been essential tools for individuals with disabilities, yet they often lack the advanced features and user-centric design needed for optimal functionality. That’s where our Smart Wheelchair steps in, offering a revolutionary solution for individuals with disabilities and older adults. With high-tech stuff like sensors, smartphone control, voice command, GPS, and stair climbing mechanism, this wheelchair is a game-changer. It’s incredibly convenient and safe, making mobility easier and more enjoyable. By emphasizing quality materials and ongoing research, this innovative wheelchair is constantly improving to meet the evolving needs of its users. Therefore, purchasing our Smart Wheelchair isn’t just about buying a product, it’s an investment in improved mobility and satisfaction. So, whether you’re navigating busy streets or tackling uneven terrain, the Smart Wheelchair is there to make your journey easier and more enjoyable.